We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
66
3
avatar

x+ky=1 is a tangent to the circle (x+3)^2 + (y-2)^2 = 16, find the value of K.

 Jun 5, 2019

Best Answer 

 #3
avatar+22363 
+4

x+ky=1 is a tangent to the circle (x+3)^2 + (y-2)^2 = 16, find the value of K.

 

\(\begin{array}{|rcll|} \hline \mathbf{(x+3)^2 + (y-2)^2} &=& \mathbf{16} \quad |\quad x+ky=1 \text{ or } \mathbf{x = 1-ky} \\ ( 1-ky+3)^2 + (y-2)^2 &=& 16 \\ ( 4-ky)^2 + (y-2)^2 &=& 4^2 \\ 4^2-8ky+k^2y^2+y^2-4y+4 &=& 4^2 \\ -8ky+k^2y^2+y^2-4y+4 &=& 0 \\ y^2(1+k^2)-4y(1+2k)+4 &=& 0 \\\\ y &=& \dfrac{4(1+2k)\pm \sqrt{4^2(1+2k)^2-4(1+k^2)4} }{2(1+k^2)} \\\\ y &=& \dfrac{4(1+2k)\pm 4 \sqrt{(1+2k)^2-(1+k^2)} }{2(1+k^2)} \\\\ y &=& \dfrac{4(1+2k)\pm 4 \overbrace{\sqrt{\color{red}(1+2k)^2-(1+k^2)}}^{=0~(\text{tangent}) } }{2(1+k^2)} \\\\ \mathbf{\color{red}(1+2k)^2-(1+k^2)} &=& \mathbf{0}\\ 1+4k+4k^2-1-k^2 &=& 0 \\ 4k+4k^2 -k^2 &=& 0 \\ 3k^2 +4k &=& 0 \\ k(3k +4 ) &=& 0 \\ && 1.)~ \mathbf{k = 0} \\ && 2.)~ 3k +4 = 0 \\ && \quad ~ \mathbf{k = -\dfrac{4}{3}} \\ \hline \end{array}\)

 

The value of k is \(\mathbf{0}\) or \(\mathbf{-\dfrac{4}{3}}\)

 

laugh

 Jun 5, 2019
 #1
avatar
+1

\(P(1;2)\\ k\ →\ \frac{1}{ ∞ }\)

.
 Jun 5, 2019
 #1
avatar
0

\(P(1;2)\\ k\ →\ \frac{1}{ ∞ }\)

Guest Jun 5, 2019
 #3
avatar+22363 
+4
Best Answer

x+ky=1 is a tangent to the circle (x+3)^2 + (y-2)^2 = 16, find the value of K.

 

\(\begin{array}{|rcll|} \hline \mathbf{(x+3)^2 + (y-2)^2} &=& \mathbf{16} \quad |\quad x+ky=1 \text{ or } \mathbf{x = 1-ky} \\ ( 1-ky+3)^2 + (y-2)^2 &=& 16 \\ ( 4-ky)^2 + (y-2)^2 &=& 4^2 \\ 4^2-8ky+k^2y^2+y^2-4y+4 &=& 4^2 \\ -8ky+k^2y^2+y^2-4y+4 &=& 0 \\ y^2(1+k^2)-4y(1+2k)+4 &=& 0 \\\\ y &=& \dfrac{4(1+2k)\pm \sqrt{4^2(1+2k)^2-4(1+k^2)4} }{2(1+k^2)} \\\\ y &=& \dfrac{4(1+2k)\pm 4 \sqrt{(1+2k)^2-(1+k^2)} }{2(1+k^2)} \\\\ y &=& \dfrac{4(1+2k)\pm 4 \overbrace{\sqrt{\color{red}(1+2k)^2-(1+k^2)}}^{=0~(\text{tangent}) } }{2(1+k^2)} \\\\ \mathbf{\color{red}(1+2k)^2-(1+k^2)} &=& \mathbf{0}\\ 1+4k+4k^2-1-k^2 &=& 0 \\ 4k+4k^2 -k^2 &=& 0 \\ 3k^2 +4k &=& 0 \\ k(3k +4 ) &=& 0 \\ && 1.)~ \mathbf{k = 0} \\ && 2.)~ 3k +4 = 0 \\ && \quad ~ \mathbf{k = -\dfrac{4}{3}} \\ \hline \end{array}\)

 

The value of k is \(\mathbf{0}\) or \(\mathbf{-\dfrac{4}{3}}\)

 

laugh

heureka Jun 5, 2019

5 Online Users

avatar